UPEX user participation by example. - Erfurth, Ivonne (Software engineering notes.)
The failure of projects is often based on difficulties in the direct and indirect communication between developer and customer teams. For the customer it is hard to understand the frequently used terms, process models, and technological concepts. Developers have a hard time to understand domain specific processes and structures, and exhibit a tendency to abstract concrete examples to higher level constructs. This makes it difficult for the customer team to understand the developing architecture and processes, and to match their needs and intentions, during evaluation phases, to seemingly unrelated generalised drawings and specifications. This set of problems is especially hard to avoid during the development of dynamic, distributed systems with multiple nodes and possibly asynchronous behaviour.Our research tries to mediate in this conflict by providing a customer-friendly reference model as basis of communication in early development phases. This model presents and simulates the dynamic aspects of (distributed) systems without immediate abstraction from examples and allows for a stepwise generalisation and evaluation with help of the customer team. In its final version the reference model will serve as a requirements statement for the professional developer.